529POsimertinib for patients with EGFR-mutant advanced NSCLC and asymptomatic brain metastases: An open-label, two-arm, phase II study. (24th November 2019) - Gillis, R; Peled, N; Goldshtien, I; Rotem, O; Rozenblum, A B; Nechushtan, H; Chen, L; Dudnik, E; Zer, A; Yust-Katz, S; Shelef, I; Roisman, L C; et al.
Abstract: Background: Osimertinib is an EGFR TKI selective for both EGFR TKI sensitizing and Thr790Met resistance mutations. While intracranial activity of osimertinib has been observed in patient subgroups within larger trials, a study focusing exclusively on patients with brain metastases has not yet been reported. We assessed the intracranial activity of osimertinib in EGFR-mutant, NSCLC patients with asymptomatic brain metastases, either as first-line therapy or following progression in pre-treated Thr790Met-positive patients. Methods: In this phase 2, open-label, two-arm study we enrolled patients with EGFR-mutant, metastatic NSCLC and at least one asymptomatic brain metastasis of 4 mm or larger in diameter. Treatment-naïve patients (arm A) and Thr790Met-positive patients who progressed on EGFR-TKI therapy (arm B) received osimertinib 80 mg once daily. Dose escalation to 160 mg once daily was performed in cases of intracranial progression without symptomatic systemic progression. The primary endpoint in both arms was intracranial metastasis response. Here we present a preliminary analysis upon the trial outstanding results. Results: Between 31/05/16 - 30/08/18 (data cutoff) 21 patients with asymptomatic brain metastases started osimertinib treatment (arm A = 15, arm B = 5 arm C = 1). Median duration of follow-up was 43 weeks. Intracranial response was achieved in 11 (73%; 95% CI 45%-92%) of 15 treatment-naïve patients (arm A) and in four (80%; 95% CI 28%-99%) of five previously treated Thr790Met-positive patients (arm B). Dose escalation was performed in four patients (arm A = 2, Arm B = 2), with one continuous response. 10 of 15 patients (67%) in arm A and 1 of 5 patients (20%) in arm B continue responding to osimertinib 80 mg at data cutoff. Toxicity side effects were similar to previously reported studies. Conclusions: Osimertinib shows equal intracranial and systemic activity with minor side effects in EGFR-mutant, treatment-naïve NSCLC and in previously treated Thr790Met-positive patients. Therefore, we suggest that osimertinib is a reasonable first treatment option for patients with EGFR-positive NSCLC and newly diagnosed asymptomatic brain metastases, and may postpone or even defer the need for brain irradiation. Clinical trial identification: NCT02736513. Legal entity responsible for the study: Nir Peled. Funding: AstraZeneca. Disclosure: N. Peled: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: BI, BMS, Lilly, MSD, Novartis, Pfizer, Roche, FMI, NovellusDx, Gaurdant360, Takeda. E. Dudnik: Advisory / Consultancy, Travel / Accommodation / Expenses: BI, Merck/MSD, Roche Pharmaceuticals, AstraZeneca. All other authors have declared no conflicts of interest.